Specifically targeted antimicrobial peptides synergize with bacterial-entrapping peptide against systemic MRSA infections - Bocheng Xu; Lin Wang; Chen Yang; Rong Yan; Pan Zhang; Mingliang Jin; Huahua Du; Yizhen Wang (Journal of Advanced Research)
Introduction: The design of precision antimicrobials aims to personalize the treatment of drug-resistant bacterial infections and avoid host microbiota dysbiosis. Objectives: This study aimed to propose an efficient de novo design strategy to obtain specifically targeted antimicrobial peptides (STAMPs) against methicillin-resistant Staphylococcus aureus (MRSA). Methods: We evaluated three strategies designed to increase the selectivity of antimicrobial peptides (AMPs) for MRSA and mainly adopted an advanced hybrid peptide strategy. First, we proposed a traversal design to generate sequences, and constructed machine learning models to predict the anti-S. aureus activity levels of unknown peptides. Subsequently, six peptides were predicted to have high activity, among which, a broad-spectrum AMP (P18) was selected. Finally, the two targeting peptides from phage display libraries or lysostaphin were used to confer specific anti-S. aureus activity to P18. STAMPs were further screened out from hybrid peptides based on their in vitro and in vivo activities. Results: An advanced hybrid peptide strategy can enhance the specific and targeted properties of broad-spectrum AMPs. Among 25 assessed peptides, 10 passed in vitro tests, and two peptides containing one bacterial-entrapping peptide (BEP) and one STAMP passed an in vivo test. The lead STAMP (P18E6) disrupted MRSA cell walls and membranes, eliminated established biofilms, and exhibited desirable biocompatibility, systemic distribution and efficacy, and immunomodulatory activity in vivo. Furthermore, a bacterial-entrapping peptide (BEP, SP5) modified from P18, self-assembled into nanonetworks and rapidly entrapped MRSA. SP5 synergized with P18E6 to enhance antibacterial activity in vitro and reduced systemic MRSA infections. Conclusions: This strategy may aid in the design of STAMPs against drug-resistant strains, and BEPs can serve as powerful STAMP adjuvants.